Equality, equity, and distributive justice: Background paper to Te Tai Waiora: Wellbeing in Aotearoa New Zealand 2022 - Chris Thompson (New Zealand Government, The Treasury, 2022)
This paper provides a survey of the literature, addressing what is meant by concepts such as 'equality' and 'equity', and reasons why economic inequality might be problematic.
Keywords: 330; Verteilungsgerechtigkeit; Soziale Gerechtigkeit; Neuseeland